Heavy Netals determination in Tea and its removal utillising Cattals, Typha Spp - Liew, Sharain Yen Ling; Chong, Harry Lye Hin; How, Siew Eng (Universiti Malaysia Sabah, 2008)
In this work, dried Typha angustifolia (T A) leaves also known as the common cattail were used as an adsorbent in Pb(II) adsorption in synthetic aqueous solutions. Adsorption studies were conducted in batch mode. Batch adsorption studies using T A were conducted and proved to be able to adsorb Pb(II) effectively with the optimized dosage of 0.6g. Adsorption equilibrium was achieved within 8 hours with an effective removal percentage of 86.04%. Adsorption kinetics was further evaluated using four kinetic models such as the pseudo-first order, pseudo-second order, intraparticIe diffusion and Elovich model. Fitting of the data were done based on linear regression analysis. The sorption kinetic data fitted best to the pseudo-second order model with an R2 of 0.9979 followed closely by the Elovich model with an R2 of 0.9952. For the isothenn studies, the adsorption system fitted the Langmuir model best as compared to the Freundlich, Temkin and D-R model. The R2 achieved for the Langmuir model was 0.9903. The maximum adsorption capacity calculated from the Langmuir model was 51.02 mg/g with a maximum removal after 24 hours at 89%. This proves that adsorption occurred via monolayer coverage of the adsorbate at the outer layer of the adsorbent. The optimized adsorption conditions were then applied to tea infusion that has been initially spiked with a fixed concentration of lead. Three types of brands of teas were used which were Lipton, Boh and Sabah tea. In all 3 brands, the concentration of lead found was below 0.2 mg/g. Each brand was then spiked with different concentrations of lead to investigate the effects of the presence of caffeine in tea towards the adsorption performance of the leaves. It was found that the adsorption performance of the leaves increased with increasing amounts of lead in the tea infusion which was contrary to in distilled water. The percentage of removal achieved in tea infusion was 38.22% (Lipton), 36.23% (Boh) and 29.86% (Sabah tea) as compared to water at 6% for 1000 mg/L of lead. From the study, dried Typha angustifolia successfully adsorbed lead in both water and tea infusion with the performance improving in the presence of tea.